The prophet Muhammad (PBUH) and development of Madinah - Omer, Spahic (Arah Pendidikan Sdn Bhd., 2009)
The Prophet Muhammad (pbuh) and development of Madinah attempts to identify and examine some principles of Islamic urban planning and development, which the Prophet (pbuh) under the aegis of revelation had bequeathed to the subsequent Muslim generations. This book discusses a number of vital urbanization and development issues as advanced by the Islamic perception of reality, of truth, of the world, of space and time, and which the young Muslim mind was then intensively acquainting itself with. The issues discussed are: the philosophy of the Islamic city, the mosque institution, provision of social amenities, spirituality and urban development, peaceful coexistence with the environment, housing, the marketplace, and open spaces. By exploring these subjects, the strength and soundness of the fundamentals of the first Muslim community clearly come into sight, as does the visionary disposition of the Prophet (pbuh) to leadership, sustainability and management.